Assessment of autonomic dysfunction with the COMPASS-31 and its relationship with disease activity and cardiovascular risks in patients with psoriatic arthritis - DURUÖZ, MEHMET TUNCAY (My University, 2022)
This study aimed to evaluate the autonomic dysfunction as assessed by the Composite Autonomic Symptom Score-31 (COMPASS-31) as well as its relationship with disease activity and cardiovascular risks in patients with psoriatic arthritis (PsA). This cross-sectional observational study involved 118 PsA patients (85 females, mean age 45.6 years) and 64 healthy subjects. Cardiovascular risks were recorded including body mass index (BMI), hypertension (HT), diabetes mellitus (DM), dyslipidemia, metabolic syndrome (MetS), and 10-year Framingham Risk scores (FRS) were calculated. PsA was assessed with regard to disease activity, quality of life, and function. Autonomic dysfunction was evaluated using the COMPASS-31 consisting of six subdivisions including orthostatic, vasomotor, secretomotor, gastrointestinal, bladder, and pupillomotor functions. The mean disease duration was 63.3 months. The mean total COMPASS-31 score was significantly higher in PsA patients than in controls (24.4 vs 11.1; p < 0.001), as were all sub-domain scores. COMPASS-31 scores were significantly lower in patients with DAPSA-REM and MDA. The COMPASS-31 total score showed significant correlations with scores of pain, global assessment, fatigue, function, quality of life, DAPSA, and BASDAI (p < 0.05).The presence of HT, dyslipidemia, MetS, and abdominal obesity did not significantly affect the total COMPASS-31 and sub-domain scores, except for the secretomotor scores being significantly higher in patients with abdominal obesity and MetS (p < 0.05). COMPASS-31 scores were not significantly different across the FRS risk groups. The symptoms of autonomic dysfunction are prevalent in PsA patients. High disease activity and pain have negative effects on autonomic function, and also functional impairment, fatigue, and poor quality of life are associated with autonomic dysfunction. However, the COMPASS-31 was found to be insufficient to demonstrate a clear relationship between autonomic dysfunction and cardiovascular risk.
Keywords: Tıp; Sağlık Bilimleri; Dahili Tıp Bilimleri; İç Hastalıkları; İmmünoloji ve Romatoloji; Medicine; Health Sciences; Internal Medicine Sciences; Internal Diseases; Immunology and Rheumatology; ROMATOLOJİ; Klinik Tıp; Klinik Tıp (MED); RHEUMATOLOGY; CLINICAL MEDICINE; Clinical Medicine (MED); Rheumatology; Psoriatic arthritis; Autonomic dysfunction; Cardiovascular disease; Metabolic syndrome; COMPASS-31; HEART-RATE-VARIABILITY; QUALITY-OF-LIFE; RHEUMATOID-ARTHRITIS; METABOLIC SYNDROME; EXPERT PANEL; CLASSIFICATION; NEUROPATHY; DIAGNOSIS; SEVERITY; OBESITY